Doping Induced Gap Anisotropy in Iron-Based Superconductors： a Point-Contact Andreev Reflection Study of BaFe2-xNixAs2 Single Crystals - 朱军 王钊胜 王震宇 侯兴元 罗会仟 鲁兴业 李春红 单磊 闻海虎 任聪 (中国物理快报：英文版, 2015)
We report a systematic investigation on c-axis point-contact Andreev reflection （PCAR） in BaFe2-xNixAs2 superconducting single crystals from underdoped to overdoped regions （0.075≤ x ≤0.15）. At low temperatures, an in-gap sharp peak at low-bias voltage is observed in PCAR for overdoped samples, in contrast to the case of underdoped junctions, in which an in-gap plateau is observed. The variety of the conductance spectra with doping can be well described by using a generalized Blonder-Tinkham-Klapwijk formalism with an angle-dependent gap. This gap shows a clear crossover from a nodeless in the underdoped side to a nodal feature in the overdoped region. This result provides evidence of the doping-induced evolution of the superconducting order parameter when the inter-pocket and intra-pocket scattering are tuned through doping, as expected in the s± scenario.